KEMAMPUAN PERSEPSI RUANG DAN HUBUNGANNYA DENGAN USIA SEKOLAH SISWA - Edi Syahputra (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2010)
The aim from qualitative research to see Junior High School Students’ space perception. The subjek of this research are 26 Junior High School Students consist of the 7th , 8th and 9th class were choosen as random. The result were Junior High School Students’ space perception still low. Eventhough the space perception students of 9th class are good